Produção de fitases por fermentação em estado sólido e imobilização das enzimas por srpay drying - Delmaschio, Isabela Belei [UNESP] (2014)
This work aimed to produce phytases by thermophilic molds in solid state cultivation, using solid agro-industrial by-products as substrates, and dry the enzymes, along with xylanases, by spray-drying. Following the drying, the powders were storage and the reduction of the enzyme activities was evaluated. For the phytase production, 13 fungi were tested, and Lichthemia ramose was chosen. Xylanase was metabolized by Myceliophtora thermophila I-1D3b. All tested microorganisms belonged to the Laboratório de Bioquímica dos Processos e Microbiologia Aplicada. L. ramose was cultivated in sugar cane bagasse, Orange pulp and peel and wheat bran, while M. thermophila was cultivated in sugar cane bagasse and wheat bran, both at 45 oC. Drying experiments were done to discriminate the adjuvant able to provide the best protection to the enzymes. The tested variables were the adjuvants (brans of wheat, corn and soybean) and the air temperature at the spray dryer outlet. The temperature was not a statistically significant factor and soybean bran provided the best protection. Experiments to optimize the drying conditions for soybean bran were carried out following a response surface approach, having the outlet air temperature, the suspension flow rate and the total solid concentration as the controlled variables. The results showed that the flow rate and the solid concentration were the significant variables. The estimated optimum condition had 7,5% of solids and the flow rate was 3 mL/min. The experiment carried at this condition, at 83 oC showed 83% of retention for phytase and 85%...